2011
DOI: 10.5054/tq.2011.247706
|View full text |Cite
|
Sign up to set email alerts
|

Responding to L2 Students in College Writing Classes: Teacher Perspectives

Abstract: Response to student writing has been a research concern for composition specialists for the past several decades. However, most research to date has utilized student opinions or researcher judgments about teacher feedback, with researchers rarely consulting teachers themselves as informants. Also, first language (L1) and second language (L2) response research has been completed and disseminated in separate arenas, with little consideration given to the current blurring of boundaries in many educational context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 60 publications
1
49
0
Order By: Relevance
“…The revisions were then documented DISCUSSION Several learning theories confirm the positive effects of WCF (see Gagne, 1985;Williams & Burden, 1997;Krashen, 2003;Brown, 2007). Moreover, a number of previous research studies have also indicated the importance and the effect of corrective feedback (Ashwell, 2000;Ellis et al, 2006;Hong, 2004;Carless, 2006;Sheen, 2007;Bitchener, 2008;Van Beuningen, 2010;Purnawarman, 2011;Ferris & Roberts, 2001;Ferris, Brown, Liu, & Stine, 2011;Ferris et al, 2013;Muth'im & Latief, 2014). This present study can then be considered as giving an additional support to these theories and the previous research studies.…”
Section: Resultsmentioning
confidence: 97%
“…The revisions were then documented DISCUSSION Several learning theories confirm the positive effects of WCF (see Gagne, 1985;Williams & Burden, 1997;Krashen, 2003;Brown, 2007). Moreover, a number of previous research studies have also indicated the importance and the effect of corrective feedback (Ashwell, 2000;Ellis et al, 2006;Hong, 2004;Carless, 2006;Sheen, 2007;Bitchener, 2008;Van Beuningen, 2010;Purnawarman, 2011;Ferris & Roberts, 2001;Ferris, Brown, Liu, & Stine, 2011;Ferris et al, 2013;Muth'im & Latief, 2014). This present study can then be considered as giving an additional support to these theories and the previous research studies.…”
Section: Resultsmentioning
confidence: 97%
“…In other words, Western teachers often assume that Asian students do not want -or are unable -to think critically and instead benefit more from mastering set patterns in order to pass exams. Several studies have shown, in fact, that as a result of their preconceptions of ESL students, teachers often give feedback to L2 writers which focuses more on grammar and structure errors than on content (Ferris, Brown, Liu, & Stine, 2011;Matsuda & Matsuda, 2010).…”
Section: The Orthodoxy Of the Five-paragraph Essaymentioning
confidence: 99%
“…Ferris, Brown, Liu, and Stine (2011) argued that it was important to note the similarities between the feedback given to students writing in English as their first language and the feedback given to those writing in English as a second language.…”
Section: Essay Feedbackmentioning
confidence: 99%